Upcycling bivalve mollusk shell wastes into triple super-, mono-and di-calcium phosphates for fertilizers and mineral animal feed - Nongnuch Laohavisuti; Chaowared Seangarun; Banjong Boonchom; Pesak Rungrojchaipon; Wimonmat Boonmee; Somkiat Seesanong (Environmental Technology & Innovation, 2024)
To reduce and utilize many mollusk shell wastes, they can be transferred to calcium carbonate (CaCO 3 ) powders by mechanical grinding and then the obtained powders can be upcycled into various calcium phosphates. Triple super-, mono-and di-calcium phosphates were prepared by rapidly simple, cheap, and environmentally friendly processes using bivalve mollusk shell wastes. Triple superphosphate (TSP) powder was obtained by a reaction between phosphoric acid and mollusk shell-derived CaCO 3 powder and then was dissolved with water to classify non-soluble and soluble fractions by filtration. Non-soluble fraction was dried to obtain a gray-white powder of dicalcium phosphate dihydrate (CaHPO 4 ·2 H 2 O). The self-evaporating process recrystallized the solution fraction to get a white powder of monocalcium phosphate monohydrate (Ca(H 2 PO 4 ) 2 ·H 2 O). All synthesized calcium phosphate samples were characterized and confirmed by X-ray fluorescence, X-ray diffraction, Fourier-transform infrared spectroscopy, scanning electron microscopy, and thermal analysis. Thermogravimetric analysis (TGA) and derivative thermogravimetric analysis (DTA) were conducted to evaluate phase stability and thermal behavior. The analyses revealed the crucial influence of temperature on phase transitions and stability, providing insights into decomposition patterns and confirming phase purity. All the calcium phosphates were found to be highly purified and phosphorus-rich, making them effective for use in fertilizers and mineral animal feed. Additionally, the green and low-cost preparation of three calcium phosphates proposed in this research will be valuable for reducing waste mollusk shells by reforming them into value-added chemical products that point out the viewpoint of a zero-waste operation for obtaining sustainable development of an effective waste management and recycling technique. • CaCO 3 obtained from mollusk shell wastes is transformed into triple superphosphate (TSP). • Recrystallization of triple superphosphate led to getting high-purity compounds of mono-and di-calcium phosphates. • Calcium phosphates show high effectiveness in the specific field as mineral feed, fertilizer, and food additive. • Recycling mollusk shell wastes to calcium phosphates are sustainable development according to the BCG model
Keywords: Phosphorus and nutrient management; Materials Engineering and Processing